Numerical simulations of oceanic pCO2 variations and interactions between Typhoon Choi‐wan (0914) and the ocean. Issue 5 (30th May 2013) - Wada, Akiyoshi; Cronin, Meghan F.; Sutton, Adrienne J.; Kawai, Yoshimi; Ishii, Masao
Abstract : [1] On 19 September 2009, Typhoon Choi‐wan passed ∼40 km to the southeast of the Kuroshio Extension Observatory (KEO) surface mooring, located at 32.3°N, 144.5°E. We use an atmosphere‐wave‐ocean coupled model that incorporated an oceanic carbon equilibrium model to investigate the typhoon‐induced CO2 outgassing observed by the KEO mooring. KEO data are used to provide atmospheric surface boundary conditions for partial pressure of CO2 ( p CO 2 air  ) and to validate the numerical results. The model simulated the observed sea‐level pressure variations reasonably well, although the simulated‐typhoon translation was 3 h slower than the estimated best track. The simulation resulted in lower than observed sea‐surface temperature (SST), sea‐surface salinity (SSS), and partial pressure of surface ocean CO2 ( p CO 2 sea  ). Better agreement was found with the grid point south of the buoy that corresponded roughly to the buoy location in the simulated‐typhoon reference frame. In situ observations show CO2 outgassing during the Choi‐wan's passage. Forty percent of observed outgassing was explained by decreasing p CO 2 air  (∼20 µatm), and thus, the remainder (∼30 µatm) must be explained by increasing p CO 2 sea  . The model simulated only one third of the increase in observed surface p CO 2 sea  variation (∼9.6 µatm), suggesting that not only SST but also high salinity and dissolved inorganic carbon caused by vertical turbulent mixing and horizontal advection are important in simulating surface p CO 2 sea  variation. The simulations also reveal that surface roughness length affects surface wind asymmetry during the passage and variation in SSS and p CO 2 sea  (∼1 µatm) after the passage. Key Points: This study developes an atmosphere‐wave‐ocean‐carbon coupled model. The numerical results for Choi‐wan are validated using in situ observations. Ocean waves affect surface wind and the ocean response to Choi‐wan.